(3ChQGb EOGQjIs - (3Ydj Nda(B, (3MLGMLgs ((3YeGf(B:s (3OGQ bfOjd ddfTQ hGdJhRjY(B,s, 2008)
(3GdebOeI(B-(3GdhQbI GdChdi(B: (3egGQGJ GdYQV GdaYGd(B: (3GdJMVjQ ddYQV(B-(3bHd GdYQV(B-(3bHjd HOGjI GdYQV(B-(3HOGjI GdYQV GdaYGd(B-(3CKfGA GdYQV(B-(3UaGJ ebOe GdYQV(B-(3dZI GdYQV(B-(3hSGFd GdEjVGM(B-(3cjajI GdJYGed eY GdCSFdI(B-(3eGPG HYO?(B-(3GdhQbI GdKGfjI(B: (3GdGLJeGYGJ(B: (3ahGFO GdGLJeGYGJ(B-(3eJi Jchf GdGLJeGYGJ fGLMI(B-(3deGPG JaTd CZdH GdGLJeGYGJ(B-(3GdhQbI GdKGdKI(B: (3GdYdGbGJ GdYGeI(B: (3hSGFd GdGJUGd GdOGNdj(B-(3GdCfTWI hGdCgOGa(B-(3GdQCj GdYGe GdLeGgjQj(B-(3GdgOa hWQb GdbjGS(B-(3GdhQbI GdQGHYI(B: (3GdebGHdGJ(B: (3GdMUhd Ydi GdeYdheGJ(B-(3NWW ddebGHdI(B-(3CSFdI hELGHGJ GdebGHdI(B-(3jhe GdebGHdI(B-(3GdhQbI GdNGeSI(B: (3GdYed aj Xd XQha eJVGQHI Ch JMJ GdVZW(B: (3VZhWGJ ef GdeYjGQ GdKbjd(B-(3GdJcja eY GdVZhWGJ(B-(3GdhQbI GdSGOSI(B: (3MaR ehXajc(B: (3CTcGd GdJMajR(B-(3CgOGa GdMhGaR(B-(3GdCSS GdYdejI dfXGe GdMhGaR(B-(3GdhQbI GdSGHYI(B: (3GdJZjjQ(B: (3eGgh GdJZjjQ(B-(3GdJZjjQ aj GdbQBf GdcQje(B-(3EOGQI GdJZjjQ(B-(3CSHGH GdJZjjQ(B-(3CeKdI Ydi GdJZjjQ(B-(3GdhQbI GdKGefI(B: (3EOGQI GdhbJ(B: (3GdhbJ aj GdbQBf hGdSfI(B-(3GSJZdGd GdhbJ(B-(3egdcGJ GdhbJ(B-(3GdhQbI GdJGSYI(B: (3GdJYGed eY Sjd GdeYdheGJ GdhGQOI(B: (3JYQja(B-(3ehGUaGJ GdeYdheGJ(B-(3GdETGYGJ(B-(3cjajI GdJYGed eY GdeYdheGJ GdhGQOI(B-(3GdhQbI GdYGTQI(B: (3EOGQI GdLhOI GdTGedI(B: (3JYQja(B-(3Cge GdeUWdMGJ GdeSJNOeI(B-(3eG GdebUhO HehGUaGJ GdLhOI GdYGdejI(B-(3GdhQbI GdMGOjI YTQ(B: (3GdJacjQ GdEHOGYj(B: (3GdJacjQ NGQL GdfU(B-(3GSJKeQ GdehLhO(B-(3eQGMd GdEHOGY(B-(3CSGSjGJ GdJacjQ GdEHOGYj(B-(3GdhQbI GdKGfjI YTQ(B: (3GdJOQjH(B: (3JYQjaI(B-(3CgejJg(B-(3eQGMdg(B-(3TQhW fLGM GdHQfGeL GdJOQjHj(B-(3GdhQbI GdKGdKI YTQ(B: (3EOGQI MedGJ GdJhYjI(B: (3JYQja(B-(3CfhGY GdMedGJ(B-(3NWhW JUeje GdMedI(B-(3JMOjO GdLeghQ GdeSJgOa(B-(3JMOjO ehGRfI GdMedIs
(3HHdjhZQGajG(B: (3U(B.231s
Keywords: (3EOGQI GdGYeGds; (3GdEJUGds; (3GdYdGbGJ GdYGeIs